1990
DOI: 10.1017/s0022112090003536
|View full text |Cite
|
Sign up to set email alerts
|

Coalescence and separation in binary collisions of liquid drops

Abstract: An extensive experimental investigation of the binary collision dynamics of water drops for size ratios of 1. 0.75, and 0.5, for the Weber-number range of 1 to 100, and for all impact parameters is reported. Two different types of separating collisions, namely reflexive and stretching separations, are identified. Reflexive separation is found to occur for near head-on collisions, while stretching separation occurs for large-impact-parameter collisions. The boundaries between both of the separating collisions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
567
1
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 620 publications
(609 citation statements)
references
References 22 publications
32
567
1
9
Order By: Relevance
“…Previous studies [25][26][27] have demonstrated that droplet separation is suppressed and hence droplet coalescence is promoted by increasing the size ratio. It is known that droplet separation occurs, at relatively high Weber numbers, when the surface tension of the temporarily coalesced droplet cannot hold the excess kinetic energy of the collision.…”
Section: Collision Dynamics and Internal Mixing Of Dropletsmentioning
confidence: 98%
“…Previous studies [25][26][27] have demonstrated that droplet separation is suppressed and hence droplet coalescence is promoted by increasing the size ratio. It is known that droplet separation occurs, at relatively high Weber numbers, when the surface tension of the temporarily coalesced droplet cannot hold the excess kinetic energy of the collision.…”
Section: Collision Dynamics and Internal Mixing Of Dropletsmentioning
confidence: 98%
“…This occurs for sufficiently low viscosities and for coalescence from an initially motionless state and is a phenomenon well known from studies of droplets falling into a liquid pool [18][19][20][21][22]. An extensive experimental study of binary midair drop collisions in air was conducted by Ashgriz and Poo [17], who characterized different regimes of coalescence and separation in terms of Weber number and an impact parameter measuring the degree to which the drop centers were offset from a head-on collision. Since one of the drops was dyed, this study also revealed that for offset collisions, substantial mixing can occur within the combined drop as a result of the free-surface deformations.…”
Section: Introductionmentioning
confidence: 99%
“…An effective visualization of mixing in this case has been a simple coloring of one of the droplets [16,17]. A key observation when a small droplet coalesces with a larger one is the generation of a vortex ring [16] as the small droplet is pulled into the larger one by surface tension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At larger velocities, the liquid distorts so dramatically that there is fragmentation of the filaments forming during impact (Ashgriz & Poo 1990;Jiang, Umemura & Law 1992). The phase diagram of impacts is of central importance in different fields where coalescence is either looked for, or unwanted.…”
Section: Introductionmentioning
confidence: 99%